2012
DOI: 10.1590/s0100-06832012000600015
|View full text |Cite
|
Sign up to set email alerts
|

N2O emissions from a cultivated mollisol: optimal time of day for sampling and the role of soil temperature

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 32 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…For example, sampling at approximately solar noon (either at 12:00 or 14:00 h) would overestimate the daily mean N2O emissions by a mean of 1.7% to 282.1% for soil sample I and 8.6% to 226.7% for soil sample II. In this study, N2O fluxes were measured at 07:00, 08:00, 10:00, 12:00, 14:00, 16:00, 18:00, 20:00, 22:00, 01:00, and 03:00 h where 10:00 h was usually considered as the routine observation time applied in many research studies (Tian et al, 2012;Cosentino et al, 2012). However, the errors between the fluxes at 10:00 h and the daily mean in soil sample I mainly ranged from -24.4% to 58.6% and -47.4% to 66.2%, and varied in soil sample II from -55.0% to 47.2% and -74.3% to 85.2% for the SW and SUW treatments, respectively, which implies that errors in estimating daily mean N2O fluxes were not negligible.…”
Section: Implications For Sampling Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, sampling at approximately solar noon (either at 12:00 or 14:00 h) would overestimate the daily mean N2O emissions by a mean of 1.7% to 282.1% for soil sample I and 8.6% to 226.7% for soil sample II. In this study, N2O fluxes were measured at 07:00, 08:00, 10:00, 12:00, 14:00, 16:00, 18:00, 20:00, 22:00, 01:00, and 03:00 h where 10:00 h was usually considered as the routine observation time applied in many research studies (Tian et al, 2012;Cosentino et al, 2012). However, the errors between the fluxes at 10:00 h and the daily mean in soil sample I mainly ranged from -24.4% to 58.6% and -47.4% to 66.2%, and varied in soil sample II from -55.0% to 47.2% and -74.3% to 85.2% for the SW and SUW treatments, respectively, which implies that errors in estimating daily mean N2O fluxes were not negligible.…”
Section: Implications For Sampling Protocolsmentioning
confidence: 99%
“…For example, Denmead et al (1979) first found that N2O emission from a grass sward clearly showed the diurnal cycle and peak N2O emissions usually occurred in the afternoon. Liu et al (2010) and Lu et al (2010) found that N2O emissions exhibited a regular unimodal diurnal pattern with temperature changes, and maximum N2O values usually occurred at 16:00 h. Cosentino et al (2012) indicated that N2O fluxes measured in the morning hours (09:00 to 12:00 h) were more appropriate to represent daily mean N2O fluxes. On the other hand, Xia et al (2013) showed that sampling at 19:00 h could well represent the daily mean N2O flux from river sediment.…”
Section: Introductionmentioning
confidence: 99%
“…The soil GHG fluxes were measured in the morning hours, between 9:00 am and 11:30 am, for comparability enhancement of the data, measuring in different days [38]. The measurements were used to represent the daily average flux value [39].…”
Section: Greenhouse Gas Fluxes: Sampling and Analysismentioning
confidence: 99%
“…The similarity between the mean daily flux and a flux recorded at a specific hour of the day was assessed through a linear 260 regression following the methods of Alves et al, 2012;and Cosentino et al, 2012). All estimated fluxes were binned into one of 24, one-hour, intervals according to the hour of the day when the chamber deployment began (the 'sampling interval').…”
Section: Data Selection and Statistical Analysismentioning
confidence: 99%
“…Unfortunately, there is considerable disagreement in the literature 45 about the existence and timing of diurnal patterns of soil N2O flux. Cosentino, et al (2012) measured N2O fluxes in an unfertilized soybean crop in Argentina every three hours over three days using five soil chambers, resulting in a total of 120 flux measurements. They observed that N2O emissions exhibited a diurnal pattern and that fluxes measured from 09:00 to 12:00 were closer to the daily mean N2O emission than fluxes measured at other times.…”
mentioning
confidence: 99%